Evaluation of histopathology of cervix in women with unhealthy cervix - Rajendiran, Sathiyakala; Gopalan, Ushadevi; Karnaboopathy, Ranganathan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Carcinoma of cervix is the third most common cancer in women worldwide and most common female cancer in India. Most cervical cancers can be detected at pre-invasive state with an adequate screening and treated, preventing overt progression to invasive cancer and hence decreasing morbidity and mortality. This study was conducted to evaluate the histopathological diagnosis of cervix biopsy in unhealthy cervix and to determine the incidence of the various precancerous and cancerous lesions. Methods: It was a prospective study in the department of Obstetrics and Gynecology in a tertiary care hospital over a period of two years. 802 women with unhealthy cervix were included in the study. Punch biopsy was taken from the cervix and sent for histopathological examination. Results: Total of 802 women were included in the study. They were in the age group of 26-75years. 53.4% were in the age group of 40-49 years followed by 20% in the age group of 30-39 years. The most common finding was chronic cervicitis in 89.4% followed by CIN I in 4.1%, CIN II in 0.9% of patients, squamous cell carcinoma in 2.1% and endocervical carcinoma in 0.4%. Conclusions: Cancer cervix is an ideal malignancy for screening, can be detected early and the premalignant lesion can be treated to prevent the progress to invasive disease. Hence all women with unhealthy cervix should be subjected to punch biopsy to detect early cases of cancer & carcinoma in situ.